ANALISIS WEBSITE WIKI VERSAILLUS DENGAN MENGGUNAKAN METODE PIECES - I Ketut Sudaryana; Hadi Sanjaya; Ricky Tjong (JBASE - Journal of Business and Audit Information Systems, 2019)
The development of this age in the world is characterized by information technology. For a long time, humans can not be separated from technology. The development of Internet information technology effected the creation of the internet. The Internet sends people to communicate and search for information about anyone. How to find existing information is to open websites that exist on the internet. Website is a system where information in the form of text, images, sound, and others are presented in hypertext form. One of the websites that contain information is Versaillus. Versaillus is a website that contains information about a game called Mobile Legends and the manifold of Versaillus is a wiki’s site, but the website is not crowded by people. Therefore, the author will researching the site versaillus by using PIECES method. The results of this study can change the site versaillus to be better and better from PIECES method.